(untitled) (Stato, Chiese e pluralismo confessionale, 2017)
SOMMARIO: 1. Introduzione - 2. Misure di trasparenza adottate nell’ambito della Santa Sede- 3. Legislazione spagnola in materia di trasparenza- 4. Il nuovo Portale di Trasparenza della CEE- 5. L’Accordo tra la CEE e TIE: profilo soggettivo- 6. L’Accordo tra la CEE e TIE: profilo sostanziale - 7. Riflessioni conclusive - 8. Appendice: Testo integro dell’Accordo tra la CEE e TIE. The commitment of the Spanish Bishops’ Conference in favor of Transparency: the Transparency Portal and the Agreement with Transparency International España ABSTRACT: This paper analyzes two recent measures adopted by the Spanish Bishops’ Conference to increase its level of transparency. The first of these measures is the creation of a new Transparency Portal in which a great deal of information is collected on institutional, legal and economic aspects related both to the Spanish Bishops’ Conference itself and to other entities of the Catholic Church in Spain. As the present article shows, it is possible to establish a parallelism between the information provided on that website and some of the active publicity obligations established by Spanish Transparency Act. The second of the measures analyzed is the Agreement signed by the Spanish Bishops’ Conference and Transparency International España. Through this Agreement, the Spanish Episcopal Conference is committed to adopt measures to increase its levels of Transparency.